PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS KELAS V SD NEGERI 10 KUBANG PIPIK BASO - Hanif, Ahmad; Arwin, Arwin; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is motivated by IPS learning in class V most of them are teacher center because students are less active in finding information and many students are unable to express their ideas and opinions in learning so that students are not active in talking and opinion. These learning problems have an impact on students' interest and motivation for learning to be reduced, and learning becomes meaningless for students. The purpose of this study is to describe the improvement of student learning outcomes in civic education learning (Civics) with model Cooperative Learning Type Make A Match In class V SD Negeri 10 Kubang Pipik Baso. Key Word :Result study, IPS, model Cooperative Learning Type Make A Match